Integrated use of residues from olive mill and winery for lipase production by solid state fermentation with Aspergillus sp - Salgado, José Manuel (2014)
Two phase olive mill waste (TPOMW) is presently the major waste produced by the olive mill industry. This waste has potential to be used as substrate for solid state fermentation (SSF) despite of its high concentration of phenolic compounds and low nitrogen content. In this work, it is demonstrated that mixtures of TPOMW with winery wastes support the production of lipase by Aspergillus spp. By agar plate screening, Aspergillus niger MUM 03.58, Aspergillus ibericus MUM 03.49 and Aspergillus uvarum MUM 08.01 were chosen for lipase production by SSF. Plackett-Burman experimental design was employed to evaluate the effect of substrate composition and time on lipase production. The highest amounts of lipase were produced by A. ibericus on a mixture of TPOMW, urea and exhausted grape mark (EGM). Urea was found to be the most influent factor for the lipase production. Further optimization of lipase production by A. ibericus using a full factorial design (32) conducted to optimal conditions of substrate composition (0.073 g urea/g and 25% of EGM) achieving 18.67 U/g of lipolytic activity.